Problematic Pornography Use in Japan: A Preliminary Study Among University Students - Okabe, Yushun; Takahashi, Fumito; Ito, Daisuke (Frontiers in Psychology, 2021)
Background Problematic pornography use is considered an addictive behavior, which is an important clinical issue. Despite considerable research interest in problematic pornography use worldwide, to the best of our knowledge, there are no extant studies on the subject in Japan. Therefore, despite the fact that many people in Japan use pornography, the difference between problematic and non-problematic users among Japanese people is not known. Objective This study aimed to identify the characteristics of problematic pornography use among Japanese students, to the best of our knowledge. Specifically, we examined general psychopathological symptoms, sexual compulsivity, depression, anxiety, and low effortful control. Methods The participants were 150 college students aged 20–26 years (mean age = 21.5, SD = 1.21, males: n = 86, females: n = 64) at a university in midland Japan. An online questionnaire was administered that included items on pornography usage patterns, impaired control of pornography use, sexual compulsivity, depression, anxiety, and effortful control. Results Most men (97%) and approximately one-third of women (35.9%) used pornography at least once in the past month. Some users reported significant daily-life problems due to difficulty in controlling pornography use (5.7%). Participants with impaired control of pornography use had higher depression, anxiety, and sexual compulsivity, and lower effortful control than pornography users without impaired control. Conclusion Some Japanese students reported significant daily-life problems due to impaired control of pornography use. The characteristics of individuals with impaired control are consistent with previous studies. The results of this study suggest that individuals with impaired control may have poor mental health, and that there is need for further research and development of treatment systems to manage this issue in Japan. Further research exploring a more varied sample in Japan is required to effectively examine problematic pornography use.